PENINGKATAN GRADE ASAP CAIR DARI TANDAN KOSONG KELAPA SAWIT MENGGUNAKAN REDISTILASI - Asmawit (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Utilization of liquid smoke products from oil palm empty fruit bunches (fibers) is currently in West Kalimantan is not optimal, and only used as a substitute for rubber coagulant formic acid. Actually liquid smoke can be upgraded into a natural food preservative. This is due to liquid smoke has the ability to preserve foodstuffs because of the acidic compounds, phenolic and carbonyl, but the scale is very small. Research on processing of liquid smoke ever done is intended for rubber farmers as a coagulant and its scale is still very small. In this research, the processing of liquid smoke with redestilation way to get a product that further adds to the benefits of liquid smoke itself as a naturally preservative.Tahu a high protein foods perishable. To inhibit such damage is often added chemical preservatives that are harmful to human health. is one type of food product that does not hold up when stored without treatment / addition of preservatives. Usually know will only hold for 1-2 days. It required a preservative that can add shelf life to know that. Chemical preservatives are relatively expensive, so we need a natural preservative that does not significantly affect health. One of these is a natural preservative liquid smoke. Therefore, the objective of this study was to determine the composition of most of the content of liquid smoke such as acetic acid and phenol. The conclusion of this study is derived liquid smoke containing 6.38% acetic acid and phenol 1.125 mg / ml.